HTTP blocking in CN: facebook.com, instagram.com, medium.com, nytimes.com, reddit.com +5 more (China) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in China. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0005. Severity: critical. Confidence: 85%